Literalmente editora: design thinking aplicado ao mercado editorial independente - Gazola, Alana Nervo (My University, 2020)
Reading is a fundamental exercise for the formulation of a critical and conscious mentality. Unfortunately, in Brazil, the reading rates are much lower than expected when compared to countries where literate culture is very widespread. It is a big mistake, to put the blame on a Brazilian publishing market with a poor or recent history. Through a retrospective research, this work rescues part of the Brazilian editorial design history and purposes the creation of an editorial service designed for nowdays, developing its books and means of contact with the reading public. All through the Design Thinking methodology, as an information mediator. [resumo fornecido pelo autor]
A leitura é um exercício fundamental para a formulação de uma mentalidade crítica e consciente. Infelizmente, no Brasil, seus índices se encontram muito abaixo do esperado quando comparados a países onde a cultura letrada é muito difundida. É um grande equívoco, pensar que o motivo recai sobre um mercado editorial brasileiro com uma história pobre ou recente. Através de uma pesquisa retrospectiva, este trabalho resgata parte da história do design editorial brasileiro e propõe a criação de um serviço editorial pensado para os dias de hoje, desenvolvendo seus livros e meios de contato com o público leitor. Tudo através da metodologia do Design Thinking, como mediador da informação. [resumo fornecido pelo autor]
Keywords: Design; Editoras particulares; Livros